Control and treatment of hepatitis by use of herbal and complementary medicine - H Fallah huseini; M Alavian (Institue of Medicinal Plants, ACECR, 2002)
Hepatitis is emerging as a serious worldwide problem. It is liver cellular, inflamation that commonly caused by alcohol, chemicals, toxins and viruses. Six different types of hepatitis viruses such as A, B, C, D, E, G, is known. They may produce the diseases together or single form. The diseases transmission is mostly following infected blood transfusion, infected syringes, and via injury and sexual behaviors. Hepatitis may manifest as hepatic fibrosis, cirrhosis, hepatocellular carcinoma, glomerulonephritis, cryoglobulinemia, porphyria and upper intestinal hemorrhage. The liver damage is due to virus activity and inflammatory changes secondary to immune activity. Hepatitis C has a latency of 10-30 years and symptoms or sings may not appear until cirrhosis is evident. This long latency time may be good opportunity for treatment of disease by use of herbal and complementary medicines. However in this review we try to investigate the efficacy of nutrition, herbal and complementary medicines in the control and treatment of hepatitis.